2014
DOI: 10.1371/journal.pntd.0002626
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences of Leptospirosis in Sri Lanka: Observations from a Flood-Associated Outbreak in 2011

Abstract: Leptospirosis is known to be an important cause of weather disaster-related infectious disease epidemics. In 2011, an outbreak of leptospirosis occurred in the relatively dry district of Anuradhapura, Sri Lanka where diagnosis was resisted by local practitioners because leptospirosis was not known in the area and the clinical presentation was considered atypical. To identify the causative Leptospira associated with this outbreak, we carried out a cross-sectional study. Consecutive clinically suspected cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 11 publications
3
91
4
Order By: Relevance
“…Control of this outbreak and treatment were a challenge to all clinicians due to two reasons; first the clinical presentation was unusual and the classical "Weil's disease" was not observed among these patients; second, diagnostic facilities were not available routinely for early diagnosis. We previously reported preliminary confirmation of the etiology of this outbreak using molecular methods, 13 which showed that there were dengue and hantavirus infections mimicking leptospirosis during this outbreak as well. 18 The purpose of the this study was to describe the clinical and biochemical features of this post-flood leptospirosis outbreak, with a particular focus on identifying the most useful laboratory methods to provide definitive, actionable diagnosis.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Control of this outbreak and treatment were a challenge to all clinicians due to two reasons; first the clinical presentation was unusual and the classical "Weil's disease" was not observed among these patients; second, diagnostic facilities were not available routinely for early diagnosis. We previously reported preliminary confirmation of the etiology of this outbreak using molecular methods, 13 which showed that there were dengue and hantavirus infections mimicking leptospirosis during this outbreak as well. 18 The purpose of the this study was to describe the clinical and biochemical features of this post-flood leptospirosis outbreak, with a particular focus on identifying the most useful laboratory methods to provide definitive, actionable diagnosis.…”
Section: Introductionmentioning
confidence: 81%
“…13 Briefly, this cross-sectional descriptive study was carried out in the Teaching Hospital Anuradhapura (THA), Sri Lanka. The study was carried out from February to May, 2011, during an outbreak of leptospirosis related to unusual heavy rains and floods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Scientifically sound data and scientific publications are lacking in Sri Lanka due to lack of laboratory diagnostic facilities and baseline data on transmission of leptospirosis. 5 Laboratory confirmation of patients with leptospirosis is important for preventing severe complications and death. 1 Most feral and domestic mammals may serve as major reservoir hosts for Leptospira.…”
Section: Introductionmentioning
confidence: 99%